Medicinalberetning for kongeriget Danmark. Medical report for the kingdom of Denmark. - Denmark. Sundhedsstyrelsen.
Title varies slightly. 1967/68- issued in 2 parts: I:sygdomme og hygiejniske forhold. Diseases, hygienic conditions. II: beretning om sygehuse og andre helbredelsesinstitutioner : Danmark uden Gronland. Report on hospitals and other institutions for the treatment of the sick in Denmark excluding Greenland. 1953-1959 issued in 2 parts: 1. Almindelige sygdomsmaessige og hygienjniske forhold o. 1. Diseases, hygienic conditions, etc. 2. Sygehuse og andre helbredelsesinstitutioner. Hospitals and other institutions for treatment of the sick. Mode of access: Internet.